Galvanic vestibular stimulator for fMRI research - Rülander, Britta Angela (2016)
This master thesis presents the further development of a galvanic vestibular stimulator for use in fMRI examinations developed in a previous thesis (MANCZAK, 2012). This thesis amends the GVS by circuits to measure feedback values and implements the stimulation circuit with digital components, such as a microcontroller and flyback integrated circuits. The microcontroller is used in order to control the current source and process the measured values. The communication between the PC, which allows user interaction through a graphical user interface, and the microcontroller is implemented through optical communication, which is defined by a communication protocol specification. The digital circuitry is designed to be placed within the MRI room, meeting the requirements imposed by strong magnetic fields and radio frequency pulses. The underlying hypothesis of the thesis is that the device can be placed within the MRI room without having a negative impact on the MRI image quality. Laboratory tests without the MRI confirmed the correct design of the galvanic vestibular stimulator.